Education Why an Informatics Degree? - Groth, Dennis P.; MacKie-Mason, Jeffrey K. (Communications of the ACM, 2010)
The article discusses what the study of informatics entails. At is essence, informatics is concerned with how people, information, and technology interact. University informatics programs are thus interdisciplinary in nature. Along with computer science, an informatics student may study any of a variety of subjects including statistics, sociology, and biology. In the baccalaureate informatics program at Indiana University Bloomington, computer programming comes last in a series of topics, rather than first. The University of Michigan has a doctoral program in informatics.